CUSTOMER SATISFACTION MEDIATES MOBILE BANKING EXPERIENCE AND SERVICE QUALITY EFFECTS ON LOYALTY - Made Kinth Nirvana Dharmawan Swarana; I Gst. A. Kt. Gd. Suasana; Ni Made Purnami; Anak Agung Gede Agung Artha Kusuma (CV. Adiba Aisha Amira, 2026)
Mobile banking has become a primary interface between banks and customers, but high digital use does not necessarily produce lasting loyalty. This study examines the effects of customer experience and mobile banking service quality on customer loyalty through customer satisfaction among users of private commercial bank applications in Denpasar City. A quantitative associative design was applied to 160 respondents selected through purposive sampling. Data were collected using a Likert scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling. The results show that customer experience and service quality positively and significantly influence satisfaction and loyalty. Satisfaction also has a positive and significant effect on loyalty. The indirect effect of customer experience on loyalty through satisfaction is 0.115 with a p value of 0.027, while the indirect effect of service quality is 0.304 with a p value below 0.001. Satisfaction functions as a complementary partial mediator in both relationships. Service quality has the strongest effect on satisfaction, indicating that reliability, responsiveness, accuracy, and transaction speed remain central to digital banking evaluation. The findings extend Expectation Confirmation Theory and provide practical guidance for strengthening mobile banking loyalty.